MADRASAH HEAD LEADERSHIP IN UPGRADING TEACHER WORK ETHOS - Hasanah, Asmaul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze how the leadership of the madrasa principal improves the professional teacher work ethic at MA Nurul Amin. This research is qualitative (case study). Research instruments using observation guides and interview guidelines. Data processing and analysis techniques were carried out through three stages: data reduction, data presentation, conclusion drawing, and data verification. The results of the study showed (1) the leadership of the madrasa head affected the work ethic of teachers (2) the improvement of the work ethic of teachers at MA Nurul Amin was quite good.